Impact of Two Antibiotic Therapies on Clinical Outcome and Gut Microbiota Profile in Liver Transplant Paediatric Candidates Colonized by Carbapenem-Resistant Klebsiella pneumoniae CR-KP - Cardile, Sabrina; Del Chierico, Federica; Candusso, Manila; Reddel, Sofia; Bernaschi, Paola; Pietrobattista, Andrea; Spada, Marco; Torre, Giuliano; Putignani, Lorenza (Frontiers in Cellular and Infection Microbiology, 2021)
Despite the colonisation by multidrug-resistant (MDR) organisms’ of liver transplant (LT) candidates significantly affects the LT outcome, to date the consensus lines for patients management are missing, including the microbiological screening indications. The aim of this pilot study is to evaluate the impact of carbapenem-resistant Klebsiella pneumoniae (CR-KP) colonisation in LT paediatric candidates to argue on optimal prevention and therapeutic strategies exploiting both clinical and microbiological approaches. Seven paediatric patients colonized by CR-KP were evaluated before and until one-year post LT. At the time of the transplant, patients were stratified based on antibiotic (ATB) prophylaxis in two groups: ‘standard ATB’ (standard ATB prophylaxis), and ‘targeted ATB’ (MDR antibiogram-based ATB prophylaxis). Twenty-eight faecal samples were collected during follow-up to perform MDR screening and gut microbiota16S rRNA-based profiling. Post-transplant hospitalization duration was comparable for both groups. No serious infections and/or complications, except for one patient, nor deaths were recorded. A progressive MDR decontamination was registered. In the ‘standard ATB’ group, overall bacterial richness increased. Moreover, 6 months since LT, Lactobacillus and Bulleidia were increased and Enterobacteriaceae and Klebsiella spp. were reduced. In the ‘targeted ATB’ group Klebsiella spp., Ruminococcus gnavus, Erysipelotrichaceae and Bifidobacterium spp. were increased 12 months after LT. In conclusion, both antibiotics prophylaxis do not affect nor LT outcomes or the risk of intestinal bacterial translocation. However, in ‘standard ATB’ group, gut microbiota richness after LT was increased, with the increase of beneficial lactic acid- and short-chain fatty acids (SCFA)-producing bacteria and the reduction of harmful Enterobacteriaceae and Klebsiella spp.. Therefore, it could be appropriate to administer a standard prophylaxis, reserving the use of ATB-based molecules only in case of complications.